Factors that contribute to financial performance of Multimedia University Cyberjaya Campus / Norzarina Md Yatim - Md Yatim, Norzarina (2013)
The Multimedia University landscape has undergone radical transformations since late 1996. It began with the establishment of private universities followed by the government's decision to allow private higher educational institutions to run 3+0 franchised programmes and the invitation made to foreign universities to set up branch campuses in Malaysia. These changes have greatly affected the provision of higher education in Malaysia. Undeniably the changes were a direct result of government policies and interventions that caused the intensified competition. These changes have forced Multimedia University, as one of the private higher educational institutions, to adopt strategic planning and management practices in ensuring their continuous growth or even survival. The most basic tenet of strategy is the fact that Multimedia University can achieve competitive advantage over rivals if Multimedia University able to distinguish itself in some ways by focusing on resources and capabilities as sources of advantage to stay relevant in the long run. Therefore, the overall goal of this study is to study the resources and capabilities of Multimedia University that form the basis of competitive advantage which in turn affect the financial performance. To carry out an in-depth study to obtain data, this study employed multi-sources approach and reinforced with evidence-based data coIlection to ensure academic rigour. In this study, Multimedia University was chosen. In addition, observation on Multimedia University facilities was also undertaken. On the whole, the findings of this study provide empirical information on the relevance of the concepts of resources and capabilities as sources of core competencies and the impact on service quality and financial performance of Multimedia University.